The influence of self-efficacy and work environment on employee performance through job satisfaction - Anita Chandra Devi; Reni Shinta Dewi (Journal of Management and Business Education)
The significant development of technology has made manufacturing companies compelled to always innovate by paying attention to their human resource management. One of the manufacturing companies in Indonesia is PT Laksana Bus Manufacture, which is engaged in bus production. The problems faced by the company are declining employee performance and the company's failure to achieve targets due to poor self-efficacy and work environment, and low job satisfaction. This study aims to determine the effect of self-efficacy and work environment on employee performance through employee job satisfaction as an intervening variable. Employing a quantitative method with SEM-PLS on 154 employees. The results indicate that self-efficacy and work environment have a significant positive effect on job satisfaction. Job satisfaction significantly positively affects employee performance and mediates the effect of self-efficacy (partial mediation) and work environment (full mediation) on performance. Self-efficacy has a significant positive direct effect on performance, but the work environment does not. PT Laksana is advised to enhance self-efficacy and create a supportive work environment. Future research is recommended to add variables and expand the sample. The results of this study provide valuable insights for business education institutions. It highlights the importance of self-efficacy, work environment, and job satisfaction in enhancing employee performance, implying that business education and corporate learning environments can be designed to build self-confidence, create a conducive learning environment, provide motivating learning experiences and performance of the employee.